Interacting constraints and relative age effect in elite cross-country skiers and freeskiers - Roaas, T.; Lorås, H.; Aune, T. K.; Flakken, B.; Dalen, T. (Journal of Human Kinetics, 2022)
Different characteristics of sports disciplines potentially lead to skewness in birth month distribution (relative age effect, RAE). These characteristics can be considered from a constraint-based approach with interacting environmental, task, and individual constraints as a theoretical framework with which to examine variations in RAE. The main aim of the present study was to examine the theoretical predictions of the constraint-based framework by investigating the birth month distribution in cross-country skiers and freeskiers at elite junior and senior levels. The sample was comprised of top ranked Norwegian U15-U19/20 cross-country skiers and junior-level freeskiers. Birth months of top ranked international senior-level skiers in cross-country and freeskiing were also collected. Results indicated an over-representation of skiers born in the first half versus the second half of the year at all junior ages in cross-country skiing. There was no significant difference in the distribution of birth months in freeskiing or in senior cross-country skiers or freeskiers. Based upon the interacting constraint framework, the skewness towards more early-born athletes in junior cross-country skiing could be due to strict age-grouped and results-oriented developmental programs beginning at an early age (environmental constraints) as well as high-demand for physical capabilities (task constraints) that favour more physically mature athletes (individual constraints). For freeskiing, the interacting environmental (less structured and more individualistic-oriented development), task (high technical/motor skill demands), and individual (no advantage of advanced physical maturation) constraints potentially operate in the opposite direction compared to cross-country skiing.